2021
DOI: 10.1186/s12576-021-00812-2
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced oxidative stress and melatonin supplementation: current evidence

Abstract: Melatonin possesses the indoleamine structure and exerts antioxidant and anti-inflammatory actions and other physiological properties. Physical exercise can influence secretion of melatonin. Melatonin is used as a natural supplement among athletes to regulate sleep cycles and protect muscles against oxidative damage. Despite decades of research, there is still a lack of a comprehensive and critical review on melatonin supplementation and physical activity relationship. The aim of this literature review is to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 126 publications
0
41
0
2
Order By: Relevance
“…Although it is mainly produced by the pineal gland and directly released into the blood or cerebrospinal fluid, melatonin is also found in several extra pineal tissues, including the brain, retina, liver, skeletal muscle, and so on ( Acuña-Castroviejo et al, 2014 ). Substantial evidence has confirmed the regulatory role of melatonin in circadian and seasonal rhythms ( Reiter et al, 2010 ; Brzezinski et al, 2021 ; Pevet et al, 2021 ; Hardeland, 2022 ), antioxidant ( Rodriguez et al al, 2004 ; Manchester et al, 2015 ; Reiter et al, 2016 ; Ortiz-Franco et al, 2017 ; Galano et al, 2018 ; Chitimus et al, 2020 ; Kruk et al, 2021 ) and anti-inflammatory effects ( Mauriz et al, 2013 ) among others. In addition to these benefits, our research group has demonstrated the ergogenic effect of melatonin in the increasing exhaustive aerobic exercise tolerance of nocturnal animals ( Beck et al, 2015A ; Beck et al, 2016 ; Faria et al, 2021 ), whereas the effect of melatonin on metabolic recovery after physical exercise is less reported.…”
Section: Introductionmentioning
confidence: 91%
“…Although it is mainly produced by the pineal gland and directly released into the blood or cerebrospinal fluid, melatonin is also found in several extra pineal tissues, including the brain, retina, liver, skeletal muscle, and so on ( Acuña-Castroviejo et al, 2014 ). Substantial evidence has confirmed the regulatory role of melatonin in circadian and seasonal rhythms ( Reiter et al, 2010 ; Brzezinski et al, 2021 ; Pevet et al, 2021 ; Hardeland, 2022 ), antioxidant ( Rodriguez et al al, 2004 ; Manchester et al, 2015 ; Reiter et al, 2016 ; Ortiz-Franco et al, 2017 ; Galano et al, 2018 ; Chitimus et al, 2020 ; Kruk et al, 2021 ) and anti-inflammatory effects ( Mauriz et al, 2013 ) among others. In addition to these benefits, our research group has demonstrated the ergogenic effect of melatonin in the increasing exhaustive aerobic exercise tolerance of nocturnal animals ( Beck et al, 2015A ; Beck et al, 2016 ; Faria et al, 2021 ), whereas the effect of melatonin on metabolic recovery after physical exercise is less reported.…”
Section: Introductionmentioning
confidence: 91%
“…Although melatonin has numerous good effects (23,66), there have been some isolated reports of a few unpleasant side effects (e.g., a modest increase in blood pressure due to nitric oxide synthase downregulation) (37,45,46,50,51). Notably, it is well recognized that diurnal melatonin ingestion in young healthy men might result in sleepiness, weariness, alertness deficiency, loss of balance, and poor coordination (35,46).…”
Section: Adverse Occurrences Related To Oral Melatonin Dosingmentioning
confidence: 99%
“…As a result, research into the antioxidant effects on exercise-induced heart injury has become a focus of interest for athletes, coaches, exercise physiologists, and free radical biologists. Numerous studies have demonstrated the potential benefits of antioxidant (including melatonin) consumption, either through food or supplementation, in reducing exercise-induced oxidative stress (22,23). However, there are still concerns and reservations about the role of melatonin in exercise physiology, despite the fact that melatonin's physiology has been thoroughly investigated in animals.…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin ( N -acetyl-5-methoxytryptamine), which is the pineal gland’s primary product, regulates circadian rhythm, sleep, and sexual behavior ( Dergaa, Varma, et al, 2021 ; Pandi-Perumal et al, 2008 ; Souissi et al, 2019 ). Melatonin is known to have antioxidant and anti-inflammatory effects ( Escames et al, 2012 ; Kruk et al, 2021 ; Souissi et al, 2018 , 2019 ; Watson et al, 2016 ). Several researchers have looked into the effects of melatonin on endurance exercise ( Alonso et al, 2006 ; Maldonado et al, 2012 ; Souissi et al, 2018 , 2019 ; Veneroso et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have looked into the effects of melatonin on endurance exercise ( Alonso et al, 2006 ; Maldonado et al, 2012 ; Souissi et al, 2018 , 2019 ; Veneroso et al, 2009 ). A single dose of exogenous melatonin, given before submaximal exercise, was reported to reduce oxidative stress, inflammation, and muscle damage ( Alonso et al, 2006 ; Kruk et al, 2021 ; Maldonado et al, 2012 ; Veneroso et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%